Association of Vitiligo with ABO/Rh System and its Influence on Thyroid Stimulating Hormone and Vitamin D - Mahmoud Ashawesh; Anfal Hareshe; Nada Alamori (AlQalam Journal of Medical and Applied Sciences, 2024)
This study was conducted to determine if there is a relationship between vitiligo and ABO blood groups, the Rhesus (Rh) factor, thyroid stimulating hormone (TSH) and vitamin D. For vitiligo analysis, two hundred subjects participated in this study, 100 vitiligo patients and 100 control cases (without vitiligo). ABO blood grouping and Rh typing were tested by a slide method. TSH testing involved 80 vitiligo patients and 80 controls (without vitiligo) and the hormone was analyzed by separating the serum in a centrifuge for two minutes and the results were obtained by Beckman fully automatic analyzer. For vitamin D, 50 vitiligo patients and 50 healthy people (without vitiligo) were included. The data on vitamin D were obtained from private laboratory services. Statistical analysis was performed using IBM SPSS version 26. P<0.05 was considered significant. Most patients with vitiligo had a significantly lower level of serum vitamin D compared with controls (p-value < 0.05), while no statistically significant difference in TSH serum levels between vitiligo cases and controls, was found (p-value > 0.05). Furthermore, despite showing that subjects with blood group O are more susceptible to vitiligo as compared to other groups, there was no significant association of vitiligo with ABO blood groups (p-value > 0.05). Similarly, the incidence of Rh positive and Rh negative was not statistically different between the two groups (p-value > 0.05). This study showed that vitiligo patients are often vitamin D deficient. This study highlights the need to evaluate vitamin D status in vitiligo patients to improve the level of skin pigment loss. It remains unknown whether vitamin D deficiency causes vitiligo. However, a collection of larger sample sizes of different ethnicities should be required to achieve a precise conclusion. البهاق هو مرض جلدي مناعي ذاتي، يتميز بفقدان لون الجلد (الصباغ) ويؤثر على حوالي 1-2٪ من سكان العالم. البهاق ليس مرضًا معديًا ويمكن أن يؤثر على جميع الأعمار من كلا الجنسين. على الرغم من الأبحاث العديدة التي تم نشرها حول البهاق، إلا أن أسباب المرض نفسه تظل غامضة. من الواضح أن حالات البهاق في منطقة طرابلس - ليبيا تزايدت في السنوات الأخيرة ولذلك قمنا بهذه الدراسة لفهم سبب هذا المرض الجلدي. الهدف من هذه الدراسة هو تحديد ما إذا كانت هناك علاقة بين البهاق وفصائل الدم ABO وعامل الريسوس (Rh) والهرمون المحفز للغدة الدرقية (TSH) وفيتامين د. لتحليل البهاق، شارك في هذه الدراسة مائتي شخص، 100 مريض بالبهاق و 100 حالة سيطرة (بدون البهاق). تم اختبار فصائل الدم ABO والعامل Rh بطريقة الشريحة. شمل اختبار هرمون الغدة الدرقية 80 مريضاً بالبهاق و 80 حالة سيطرة (بدون البهاق) وتم تحليل الهرمون عن طريق فصل المصل في جهاز الطرد المركزي لمدة دقيقتين وتم الحصول على النتائج بواسطة محلل بيكمن الآلي بالكامل. بالنسبة لفيتامين د، تم تضمين 50 عينة لمرضي بالبهاق و50 شخصاً سليماً (ليس لديهم البهاق). تم الحصول على البيانات المتعلقة بفيتامين د من خدمات المختبرات الخاصة. تم إجراء التحليل الإحصائي باستخدام SPSS الإصدار 26. واعتبر P>0.05 مهمًا ذو دلالة إحصائية. كان لدى معظم المرضى الذين يعانون من البهاق مستوى أقل بكثير من فيتامين د في الدم مقارنة مع مجموعة التحكم (قيمة الدالة الإحصائية p>0.05)، في حين لم يتم العثور على فروق ذات دلالة إحصائية في مستويات هرمون الغدة الدرقية بين حالات البهاق والمجموعة الضابطة (قيمة p<0.05). علاوة على ذلك، على الرغم من إظهار أن الأشخاص ذوي فصيلة الدم O هم أكثر عرضة للإصابة بالبهاق مقارنة بالمجموعات الأخرى، لم يكن هناك ارتباط كبير بين البهاق وفصائل الدم ABO (القيمة p<0.05)، لم يكن معدل Rh الإجابي و السلبي ذو إختلاف كبير ما بين المجموعتين 96%، 4% في مرضى البهاق مقارنة بـ 90%، 10% في السيطرة على التوالي و هذا الإختلاف لم يكن أيضا ذو دلالة إحصائية (قيمة p<0.05). أظهرت هذه الدراسة أن مرضى البهاق غالبا ما يعانون من نقص فيتامين د. تسلط هذه الدراسة الضوء على الحاجة إلى تقييم حالة فيتامين د لدى مرضى البهاق لتحسين مستوى فقدان صبغة الجلد. لا يزال غير معروف ما إذا كان نقص فيتامين د يسبب البهاق. لذلك في المستقبل، ينبغي أن تكون هناك حاجة إلى تجميع أعداد أكبر من العينات من مختلف الأعراق للوصول إلى نتيجة دقيقة